Določitev karakterističnih notranjih statičnih količin cestnih mostov iz podatkov tehtanja vozil med vožnjo - Žnidarič, Aleš (Gradbeni vestnik, 2022)
The paper deals with the determination of the internal forces and moments in road bridges from the weigh-in-motion (WIM) data. WIM measurements are the only means that provide a comprehensive and unbiased picture of freight traffic on a me- asured road section. The WIM results are crucial for calculating the actual effects of traffic loads, a key parameter in assessing the structural safety of old and deteriorated bridges. Such bridges would often be closed or moved when analysed with load models from the current design codes. The paper presents methods for calculating the characteristic values of load actions calculated using WIM data. We focused on the convolution method and compared the results with the extreme value extra- polations, the most common procedure for predicting the maximum expected impact of traffic load, and extensive numerical simulations. We paid close attention to the selection of input parameters and the determination of characteristic values that significantly affect the extrapolation and simulation results. Finally, we have shown that the convolution method, which is com- putationally far less demanding than other more commonly used methods, yields comparable results, which are, at the same time, less sensitive to the subjective choice of parameters. The main conclusion of the research is that for a reliable calculation of the characteristic static internal forces and moments in road bridges, we need WIM-measured axle loads and spacings of at least 100,000 heavy goods vehicles.
Keywords: bridge; B-WIM; convolution; internal forces and moments; konvolucija; most; notranje statične količine; odprti dostop; open access; simulacija; simulation; tehtanje vozil med vožnjo; weigh-in-motion; WIM